“Inside-out Leadership” Toward Developing Efficacious Leaders Among Academic Deans in State Universities and Colleges - Melon-Galvez, S (KnE Social Sciences, 2018)
Understanding job performance of academic deans is essential to managing organizations. It is therefore significant to find out job performance of the immediate leaders to measure productivity at work. Learning to navigate within the broader organizational environment and the significant changes in the nature of their work makes academic dean position stressful and difficult. Along the emotional struggles are with a great sense of loneliness and isolation. Academic deans must turn such struggles into enjoyable tasks because they need to man educational organizations and hold responsible of the activities to achieve the goals placed on their hands. The problem of a dean’s multitudinous responsibilities seemed apparent in modern day educational setting. State Universities and Colleges (SUCs) Region III academic deans were not differently far from the academic deans in general. This research regional in scope was done with the aim at finding out the relationship between Inside-out Leadership and Self-efficacy to the Job Performance of Academic Deans in State and Universities and Colleges (SUCs) in Region III for the A.Y. 2016- 2017. The correlational approach was utilized in this study with three questionnaires using RSLQ for Self-efficacy, GSEQ for Self-efficacy, and APR: Dean Evaluation Process Questionnaire for Job Performance as the instruments used in gathering the pertinent data. Findings revealed that ADs were highly efficacious, and were using inside-out strategies to a great extent but the latter skills were not significant to their job performance. Keywords: inside-out leadership, self-efficacy, academic deans, job performance